Extratos vegetais na germinação de sementes de Baccharis dracunculifolia e Plantago lanceolata - Conceição, Danila Monte [UNESP]; Lorenzetti, Emi Rainildes; Rigotti, Marcelo [UNESP]; Sacramento, Luis Vitor Silva do [UNESP]; Rodrigues, Joao Domingos [UNESP] (My University, 2010)
The objective of this study were to evaluate the activity of ethanolic extrats of eucalyptus leaves (Corymba citridora), yarrow leaves (Achillea millefolium) and bitter melon leaves and stems (Momordica charantia) in the germination of Baccharis dracunculifolia and Plantago lanceolata. The germination was monitored every two days, and incubated for a period of 14 days. Was obtained the percentage of germination, the rate of speed of germination (IVG) and the average time of germination (TMG). The extrats had allelopathic action in B. dracunculifolia and P. lanceolata seeds, M. charantia and A. millefolium extrats inhibited the germination. In P. lanceolata seeds, C. citriodora and A. millefolium inhibited completely the seeds germination, showing effient allelopathic effects.

Objetivou-se no presente estudo avaliar a atividade alelopática dos extratos etanólicos de folhas de eucalipto (Corymbia citriodora), milfolhas (Achillea millefolium) e folhas e ramos de melão de São Caetano (Momordica charantia) sobre a germinação in vitro de Baccharis dracunculifolia e Plantago lanceolata. A germinação foi acompanhada a cada dois dias, constando um período de 14 dias de avaliação. Foram obtidos a porcentagem de germinação, o índice de velocidade de germinação (IVG) e o tempo médio de germinação (TMG). Os extratos de M. charantia e A. millefolium inibiram a germinação. Em sementes de P. lanceolata, os extratos de C. citriodora e A. millefolium inibiram completamente a germinação das sementes. O extrato de C. citriodora demonstra um efeito alelopático eficiente em condições in vitro.
Keywords: Baccharis dracunculifolia; Plantogo lanceolata; Medicinal plants; Allelopathy; Baccharis dracunculifolia; Plantago lanceolata; Plantas medicinais; Alelopatia